Prenatal Brain Imaging in Isolated vs. Complicated Club Foot: A Cohort Study - Gat, I.; Bar Yosef, O.; Hoffmann, C.; Lebovitz, O.; Shashar, D.; Gilboa, Y.; Yagel, I.; Achiron, R.; Katorza, E. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
Purpose: Talipes equinovarus (TEV) is a common birth defect. Differentiation between isolated and complex TEV is fundamental due to its effect on prognosis. Association between TEV and poor neurological outcome is more prominent in complex cases and highlights the significance of brain evaluation. The aim of the current study was to evaluate the contribution of fetal brain MRI to sonographic evaluation.Materials and Methods: In this retrospective study we evaluated charts of all pregnant patients referred for fetal brain MRI due to fetal TEV between 1/1/2011 and 12/31/14 in a single tertiary referral center. Isolated and complex TEV were differentiated according to associated anomalies. Brain US and MRI results were compared.Results: 28 pregnant patients were included with an average gestation and parity of 2.5 and 1.5, respectively. Both isolated and complicated TEV groups included 14 fetuses after initial TEV diagnosis on anatomical survey. Brain sonography and MRI were normal among 12/14 patients with isolated TEV while two patients were later diagnosed with mild ventriculomegaly. US brain evaluation has revealed pathologic findings in 4 (28.6 %) cases in the complicated TEV group, while MRI demonstrated abnormal findings in 8 (57.1 %) fetuses with notable severity diversity. In 6 cases, MRI diagnosed additional pathologies which were not demonstrated by US.Conclusion: Brain fetal MRI is an efficient tool during antenatal evaluation of complicated TEV with a high percentage of additional findings not demonstrated songraphically while its efficacy in isolated cases is in doubt. The current study expands the relevance of fetal brain MRI in cases of non-CNS anomalies.
Keywords: club foot; talipes equinovarus; prenatal imaging; fetal brain MRI; neurosonogram